CONSUMER SATISFACTION AND TRUST TO DETERMINE THE RETURNING VISIT INTENTION THE HEALTH CLINIC - Ardhitya Alam Wiguna; Linda Ekadewi Widyatami; Rizal Perlambang CNAWP (SEAN Institute, 2023)
The service industry understands the needs and desires of consumers is an important point, especially in health clinics. In an increasingly competitive environment, the primary concern for practitioners is attracting new consumers through marketing and motivating them to make repeat purchases through service efforts/strategies. The characteristics of service quality at health clinics are different from other products/services, so they require specific measurements by distinguishing the perception of medical quality from the perception of service quality. This study aims to identify the relationship between perception of medical quality, perception of service quality, fairness of price, satisfaction, trust, and intention to revisit health clinics by proposing and testing theoretical models. This research was conducted at several health clinics in several cities in East Java. Data collection is carried out by providing questions through questionnaires given to respondents. A total of 220 valid data were collected and analyzed using Structural Equation Model analysis with Amos 24 software. The findings show that the perception of medical quality, perception of service quality, perception of price fairness have a significant influence on consumer satisfaction, and satisfaction and trust act as significant mediators of the returning visit intention the health clinic.